The Effect of Microwave Heating Time on the Optical Properties of CDs from Soursop Leaves Based on UV-Vis Spectrum Analysis - Buky Wahyu Pratama; Ni'matul Azizah; Fathan Hanifi Mada Mahendra; Wipsar Dwandaru (Department of Mechanical Engineering, Faculty of Engineering and Computer Science, Universitas Global Jakarta, 2025)
This study investigated the effect of microwave heating duration on the optical properties of Carbon Dots (CDs) synthesized through a green synthesis using soursop leaf extract (Annona muricata L.) as a natural carbon precursor. The synthesis process was carried out using microwave-assisted carbonization with heating durations of 0 minutes (Non), 10 minutes (T10), and 20 minutes (T20) to evaluate the influence of reaction time on the optical characteristics. UV–Vis spectroscopic analysis was performed at a wavelength range of 200–800 nm to determine the absorption of resulting CDs. The spectrum showed that the absorbance intensity increased significantly with longer microwave heating times, with a dominant peak observed around 280 nm, corresponding to the π–π* electronic transition of aromatic C=C bonds. Transitions from heteroatom-containing groups such as C=O or C–N can be seen at a weak shoulder around 320–350 nm, which was attributed to n–π*. The increased absorption intensity at T20 indicates a higher degree of conjugation and carbonization, showing more developed sp² domains within the CDs. This research demonstrates that microwave heating duration tunes the optical and electronic properties of the synthesized CDs, offering potential control of band structure and absorption for future applications in photonic and optoelectronic materials.